Comparando as Interfaces de Programação Paralela OpenMP e TBB em um Benchmark - Fan, Henrique; Furquim, Jian; Schepke, Claudio (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2019)
This paper aims to analyze the parallel programing interfaces OpenMP and Intel Threading Building Block (Intel TBB) in a new benchmark composed by a set of applications. The execution times obtained in five applications were compared using the two interfaces, along with the sequential versions of the algorithms. The paper evaluates the parallelization strategy of each interface. The results obtained showed that in the majority of tests performed OpenMP had a better result than TBB. The TBB interface obtained results very close to those of OpenMP in most applications.